FORMING CHILDREN’S SPEECH WITH THE HELP OF FAIRY TALES - Ergasheva , Sabina Qobil qizi; G‘ulomova , Sevara Ulug‘bek qizi; Shermamatova , Zaynab Azimjonovna (Educational Research in Universal Sciences, 2023)
This article delves into the profound impact of fairy tales on children’s speech development, emphasizing the pivotal role of early language exposure. It explores the cognitive and linguistic benefits of fairy tales, their influence on speech fluency and articulation, and their cultural and emotional engagement. Additionally, the article offers insights into leveraging fairy tales for language intervention, fostering metacognitive skills, and creating a rich storytelling environment at home. By showcasing the transformative power of fairy tales, this piece highlights the enduring value of these narratives in shaping children’s linguistic abilities and nurtures an appreciation for diverse storytelling traditions across cultures.